Design and Development of Hybrid Electric Vehicle Rear Diffuser - R. A., Bakar; D., Ramasamy (2008)
Next in line for alternatives, hybrid electric vehicles (HEV) are the most logical step in reducing pollutions. However, an efficient model needs to be developed which can adapt latest technologies so that the vehicle is more efficient on the road. Under the program of “Series Hybrid Vehicle Cost-Effective Powertrain Components Development” some aerodynamic studies were carried out. The aim was to reduce energy consumption of the battery module by reducing wind drag and weight while retaining the original structure of the model. In the attempt to reduce the drag of the vehicle certain aerodynamic modifications was targeted. The modifications were investigated so that only proven results were chosen for the model. One of these modifications is the rear diffuser. Its idea was to reduce lift of the car and also some weight from the luggage compartment. The task was done by doing a computational fluid dynamic (CFD) analysis for expected vehicle speed of 50-100 km/h. A drag force was found based on Finite Element Method (FEM) based on inputs from CFD. This force was calculated to produce the drag coefficient of the car as a whole. The approach needed to justify the amount of drag that can be reduced by addition of a rear diffuser as compared to the model without a diffuser. Pressure profile of the model was analysed together with velocity plot around the model. The reduction of lift and flow separation is the key results that will be a point of discussion. The justification made enabled the design to proceed on the actual car.